1998
DOI: 10.3354/meps167227
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of microhabitat use on large-scale adult abundance in two families of Caribbean reef fishes

Abstract: An important question for ecologists is whether the processes that influence the distribution of organisms at small spatial scales also influence the variation in abundance at larger scales. I examined the relationship between microhabitat use by individual fishes and variation in abundance among sites for the adults of 11 species of Caribbean reef fishes (6 pomacentrids and 5 scarids). At the level of individual microhabitat use, all species associated with certain substrata(um) more than would be expected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…In our study, however, no significant correlations were found between abundances of 2 of the Centropyge species and their commonly used micro-habitat, as has been found for other coral reef species (Tolimieri 1998, but see Robertson & Sheldon 1979. Instead, Centropyge bicolor abundances were correlated with the percentage cover of sand and rubble, a substratum category found in lower proportions in home patches than elsewhere.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, however, no significant correlations were found between abundances of 2 of the Centropyge species and their commonly used micro-habitat, as has been found for other coral reef species (Tolimieri 1998, but see Robertson & Sheldon 1979. Instead, Centropyge bicolor abundances were correlated with the percentage cover of sand and rubble, a substratum category found in lower proportions in home patches than elsewhere.…”
Section: Discussioncontrasting
confidence: 50%
“…For example, Tolimieri (1998a) showed that large-scale patterns of adult abundance in a parrotfish and 4 damselfishes were related to patterns of microhabitat availability. For the damselfish Stegastes dorsopunicans, 84% of the among-reef variance was explained by availability of preferred microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…While the literature is replete with studies of fish-habitat associations, most of these studies are conducted at a single spatial scale. Thus the degree to which among-reef patterns of abundance are predicted by among-reef variability in the amount of appropriate microhabitat is largely unknown (but see Tolimieri 1995, 1998a,b, Caselle & Warner 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Note that this study does not attempt to provide insights into the detailed mechanisms causing the variations in fish abundances, which will be a complex combination of factors such as settlement and post-settlement habitat choices and subsequent survival (e.g. Tolimieri 1998, Schmitt et al 1999, White & Warner 2007, Shima et al 2008. We link habitat quality to adult and juvenile fishes separately because different life-phases within an ecological community may have different habitat requirements (Almany 2004a).…”
mentioning
confidence: 99%